Novel regulatory systems for acetylcholine release in rat striatum and anti‐Alzheimer's disease drugs. Issue 5 (7th May 2019) - Muramatsu, Ikunobu; Uwada, Junsuke; Yoshiki, Hatsumi; Sada, Kiyonao; Lee, Kung‐Shing; Yazawa, Takashi; Taniguchi, Takanobu; Nishio, Matomo; Ishibashi, Takaharu; Masuoka, Takayoshi
Abstract: Regulation of neurotransmitter release in the central nervous system is complex. Here, we investigated regulatory mechanisms for acetylcholine (ACh) release from cholinergic neurons by performing superfusion experiments with rat striatal segments after labelling the cellular ACh pool with [ 3 H]choline. Electrical stimulation‐evoked pronounced [ 3 H]ACh release from cholinergic neurons. The estimated quantity of [ 3 H]ACh release per pulse of electrical stimulation was reduced by an increase in stimulus frequency, showing an inverse correlation between release probability of ACh and neuronal excitation. ACh release was also negatively regulated by pre‐synaptic muscarinic ACh receptors (mAChRs). The autoinhibition induced by released ACh was predominantly suppressed by the M2 ‐selective antagonist AF‐DX 116, partially inhibited by M3 ‐selective darifenacin, and minimally by M4 ‐selective PD 102807. Other subtype‐selective antagonists had no effect at subtype‐selective concentrations. ACh esterase (AChE) inhibitors (diisopropylfluorophosphate, donepezil and galantamine) at concentrations that mostly inhibit esterase activity reduced [ 3 H]ACh release, and the reduction was abolished by treatment with atropine. This implies that pre‐synaptic autoreceptors are activated more after blockade of ACh hydrolysis, leading to autoinhibition of ACh release and consequent reduction in synaptic ACh concentrations. [ 3 H]efflux was also enhanced by ACh uptake inhibitors (100 μM hemicholinium‐3 and physostigmine), regardless of ACh hydrolysis. This study shows that synaptic ACh concentrations in striatal cholinergic neurons are regulated in a complex manner by many factors such as release probability, pre‐synaptic M2 /M3 /M4 mAChRs, AChE and post‐synaptic ACh uptake, and provides important information about cholinergic neurotransmission for future exploration of therapeutic strategies for Alzheimer's and other central nervous system diseases. Open science badges: This article has received a badge for *Open Materials * because it provided all relevant information to reproduce the study in the manuscript. The complete Open Science Disclosure form for this article can be found at the end of the article. More information about the Open Practices badges can be found athttps://cos.io/our-services/openscience-badges/ . Abstract : Neurotransmitter release in the Central Nervous System is regulated in a complex manner. We proposed the following regulatory mechanisms in central cholinergic transmission: The release probability of acetyl choline (ACh) is inversely correlated with neuronal excitation. ACh release is predominantly autoregulated by M2 metabotropic ACh receptors (mAChRs), and slightly by M3 and/or M4 mAChR subtypes. Synaptic ACh concentrations are controlled by AChE and ACh transporter. ACh acts directly on the surface AChRs and also on the intracellular receptors after transportation in postsynaptic neurons. The present results provide important information for therapeutic strategies for neurodegenerative diseases including Alzheimer disease. Open Science: This manuscript was awarded with the Open Materials Badge For more information see:https://cos.io/our-services/open-science-badges/